Alloimmune Monitoring after Islet Transplantation: A Prospective Multicenter Assessment of 25 Recipients. Issue 12 (December 2016) - Delaune, Vaihere; Toso, Christian; Benhamou, Pierre-Yves; Wojtusciszyn, Anne; Kessler, Laurence; Slits, Florence; Demuylder-Mischler, Sandrine; Pernin, Nadine; Lablanche, Sandrine; Orci, Lorenzo A.; Oldani, Graziano; Morel, Philippe; et al.
Islet transplantation is an effective treatment for selected patients with type 1 diabetes. However, an accurate test still lacks for the early detection of graft rejection. Blood samples were prospectively collected in four university centers (Geneva, Grenoble, Montpellier, and Strasbourg). Peripheral blood mononuclear cells were stimulated with donor splenocytes in the presence of interleukin-2. After 24 h of incubation, interferon-γ (IFN-γ) ELISpot analysis was performed. After a total of 5 days of incubation, cell proliferation was assessed by fluorescence-activated cell sorting (FACS) analysis for Ki-67. Immunological events were correlated with adverse metabolic events determined by loss of ≥1 point of β-score and/or an increased insulin intake ≥10%. Twenty-five patients were analyzed; 14 were recipients of islets alone, and 11 combined with kidney. Overall, 76% (19/25) reached insulin independence at one point during a mean follow-up of 30.7 months. IFN-γ ELISpot showed no detectable correlation with adverse metabolic events [area under the curve (AUC) = 0.57]. Similarly, cell proliferation analysis showed no detectable correlation with adverse metabolic events (CD3 + / CD4 + AUC = 0.54; CD3 + /CD8 + AUC = 0.55; CD3-/CD56 + AUC = 0.50). CD3-/CD56 + cell proliferation was significantly higher in patients with combined kidney transplantation versus islet alone (6 months, p = 0.010; 12 months, p = 0.016; and 24 months, p = 0.018). Donor antigen-stimulated IFN-γ production and cell proliferation do not predict adverse metabolic events after islet transplantation. This suggests that the volume of transplanted islets is too small to produce a detectable systemic immune response and/or that alloimmune rejection is not the sole reason for the loss of islet graft function.